2020
DOI: 10.2807/1560-7917.es.2020.25.23.2001005
|View full text |Cite|
|
Sign up to set email alerts
|

SARS-CoV-2 infection in farmed minks, the Netherlands, April and May 2020

Abstract: Respiratory disease and increased mortality occurred in minks on two farms in the Netherlands, with interstitial pneumonia and SARS-CoV-2 RNA in organ and swab samples. On both farms, at least one worker had coronavirus disease-associated symptoms before the outbreak. Variations in mink-derived viral genomes showed between-mink transmission and no infection link between the farms. Inhalable dust contained viral RNA, indicating possible exposure of workers. One worker is assumed to have attracted the virus from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
850
4
27

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 661 publications
(942 citation statements)
references
References 17 publications
14
850
4
27
Order By: Relevance
“…Indeed, SARS-CoV-2 is already responsible for infections in various animal species. SARS-CoV-2 genomes [16,17] have been isolated from natural infections in zoo lions and tigers [15], companion animals including cats and dogs [60,61] and following widespread outbreaks in multiple mink farms in the Netherlands resulting in mass culling [62] (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SARS-CoV-2 is already responsible for infections in various animal species. SARS-CoV-2 genomes [16,17] have been isolated from natural infections in zoo lions and tigers [15], companion animals including cats and dogs [60,61] and following widespread outbreaks in multiple mink farms in the Netherlands resulting in mass culling [62] (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Minks have been showed to carry Hepatitis E virus [26], SARS-CoV-2 [27], Cryptosporidium spp. [28] and several other zoonotic pathogens [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Since the outbreak of SARS-CoV-2 was first identified in December of 2019, it has been demonstrated that SARS-CoV-2 can naturally and experimentally infect several animal species (Lakdawala and Menachery 2020;Hernandez, Abad et al 2020;Oreshkova et al 2020). There have been multiple case reports of natural transmission of the virus from humans to dogs and cats, infection of "big cats" (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…There have been multiple case reports of natural transmission of the virus from humans to dogs and cats, infection of "big cats" (i.e. a lion and tigers) at the Bronx Zoo, and mink on farms in The Netherlands, Denmark and Spain (Newman, Smith et al 2020;Leroy, Gouilh et al 2020;Oreshkova et al, 2020). In a recent animal susceptibility study, dogs, cats, ferrets, pigs, chickens and ducks were experimentally infected with SARS-CoV-2 (Shi, Wen et al 2020).…”
Section: Introductionmentioning
confidence: 99%